Формування системи обліку і контролю витрат на інновації - Гик, В. В.; Hyk, V. V. (Видавництво Львівської політехніки, 2017)
У статті з’ясовано теоретичні основи побудови системи обліку та контролю витрат на інновації, визначені підходи до її формування. Визначено, що до основних складових елементів системи обліку витрат на інновації необхідно відносити об’єкти, суб’єкти та елементи методу бухгалтерського обліку (первинні документи, облікові реєстри, звітність, рахунки обліку), які є взаємопов’язаними та взаємодоповнювальними. Запропоновано формувати системи обліку та контролю витрат на інновації як логічного комплексу етапів під впливом факторів зовнішнього та внутрішнього середовища. При цьому, мета та завдання формування такої системи повинні узгоджуватися та відповідати загальній стратегії розвитку підприємства.

Present day state of formation of accounting information about costs on innovations in managerial system has been investigated in the article. It has been determined that for successful management of an economic subject within a complex dynamic surrounding, clear and regular gathering, storage, processing and release of diversified information are required. Theoretical basis of creating accounting and control system of costs on innovations have been revealed, approaches to its formation have been determined. It has been clarified that main component units of accounting system of costs on innovations should include objects, subjects and elements of bookkeeping method (journal voucher, accounting records, financial reporting, financial accounts) which are interrelated and complementary. It has been defined that formation of the system of business accounting of costs on innovations must be provided through documentation, which plays a crucial role in enterprise management, and is an element of the accounting method, provides control over maintenance of household property and its efficient use. When you create a system of accounting for and control of expenditure on innovation is important and identifying its stages. Therefore, it is proposed to carry out the formation of a system of accounting for and control of expenditure on innovation as a logical set of stages under the influence of factors external and internal environment. It has also been suggested forming accounting and control system of costs on innovations as a logical set of stages under the influence of external and internal environment. Herewith, the purpose and objectives to form this system must be coordinated and correspond to general strategy of enterprise development. With the aim of making strategic decisions in the process of management of enterprise development accounting for the cost of innovation acquires the characteristics of a system, provided that the use of the elements of his method. Therefore, the characteristic feature is the presence of all components inherent in it. For the purposes of tactical and strategic decisions in the enterprise development management accounting costs of innovation acquires the features of the system when used elements of his method. Therefore, a feature of the system is that all inherent components. It has been defined that formation of an effective accounting system of costs on innovations is affected by external and internal factors. The influence of each factor as an inciter (promote growth) and disincentive has been clarified.
Formation of accounting and control system of costs on innovations
Keywords: витрати на інновації; системний підхід; організація; облік і контроль; costs on innovations; systematic approach; organization; accounting and control; 657.471; 657.6